Manajemen Sarana dan Prasarana Pondok Pesantren Shuffah Hisbullah Natar Lampung Selatan - Ahmad Fauzan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2018)
The aims of this study is to determine; (1) the planning and procurement of facilities and infrastructure of Pondok Pesantren; (2) distribution of facilities and infrastructure of Pondok Pesantren; (3) maintenance of facilities and infrastructure of Pondok Pesantren; (4) inventory of facilities and infrastructure of Pondok Pesantren; (5) removal of facilities and infrastructure of Pondok Pesantren. This research uses qualitative approach with descriptive design. From the analysis result concluded; (1) Needs and Procurement Analysis: (a) Planning aims to find out the facilities and infrastructure needed to achieve the vision, mission, goals and objectives of the pesantren, (b) Planning is done early in the year, (2) Distribution: (a) the purchase of facilities and infrastructure by selection, (b) distribution is distributed to each department and class program; (3) Maintenance: (a) the use of learning is tailored to the needs of teachers and students, (b) the use of discipline to be observed by santri, (4) Inventory: (a) inventory is undertaken by specialized staff, (b) recording of all items, recording of usage and recapitulation report for a year, (5) Removal: (a) deletion done with initial report making news of the event, (b) removal for unsuitable items Keyword: management, facilities and infrastructure